Plasma-derived biological medicines used to promote haemostasis - Ofosu, Frederick A.; Freedman, John; Semple, John W. (Thrombosis and Haemostasis, 2008)
Several biological medicines derived from human and animal plasmas can effectively improve haemostasis in individuals with inherited or acquired defects in haemostasis. Factor VIII and factor VIII/vWF and factor IX concentrates are used to treat haemophilia A, von Willebrand disease and hemophilia B respectively. Cryoprecipitates are used to treat hypofibrinogenemia and von Willebrand disease where desmopressin (DDAVP) is ineffective or when plasma-derived factor VIII/vWF concentrates are unavailable. Thrombin-containing topical haemostatic agents and fibrin sealants are used to control perioperative bleeding. Intravenous immunoglobulin has several uses, including management of patients with autoimmune thrombocytopenias and patients with acquired factor VIII deficiency. Similar to most protein- based biological medicines, all the above products can elicit some level of antibody response, with clinical consequences that vary from mild anaphylaxis to loss of product efficacy. An ongoing potential safety concern with any biological medicine derived from blood/plasma is transmission of blood-borne pathogens. This safety concern has lessened significantly in the past decade as a result of the institution of more effective pre- and post-donation screening that tests for potential pathogens, and institution of pathogen reduction strategies to which many plasma-derived biological medicines are now routinely subjected. This article considers the manufacture, standardization, clinical efficacy and adverse event profiles of the plasma-derived biological medicines currently used to promote haemostasis in patients with inherited or acquired functional defects in haemostasis. It also considers approaches employed to minimize infectivity of biological medicines derived from human and animal plasmas and to manage patients who develop antibodies (inhibitors) to clotting factor concentrate infusions.
Keywords: Adverse events; biological medicines; cryoprecipitate; factor VIII; factor IX; haemostasis; IVIG; thrombin